Phytoremediation uptake model of heavy metals (Pb, Cd and Zn) in soil using Nerium oleander. Issue 7 (July 2020) - Ibrahim, Naira; El Afandi, Gamal
Abstract: Phytoremediation is an important and effective tool to remove different contaminations in the soil, water and air. The main objective of this research was to evaluate the effect of phytoremediation using one species of shrubs, Nerium oleander plants, on reducing the heavy metals (HMs) contamination in the soil. The present study was carried out during 2015 in El-Dakhyla (industrial zone), Alexandria Egypt. A simple Uptake Plant Model (UPM) was used to estimate the contribution of various pathways in remediating ((Lead (Pb), Cadmium (Cd) and Zinc (Zn)) through different parts, in one of the evergreen shrubs (leaves, stem and root). These include soil-root-leaf pathway, soil-air-leaf pathway, and its deposition. The model calculations revealed that the (Root concentration Factor) log RCF of the root equals 0.5, 0.41, and 0.45, respectively. The Translocation Stem Concentration Factor (TSCF) of the upward in the xylem equals 0.85, 0.98 and 0.99. Moreover, the Bioaccumulation Factors (log BCF) of the soil is 1.32, 0.014 and 0.061. In addition, the partition coefficient of Octanol-Water (log Kow) is 4.67, 2.75, and 3.35, respectively. Therefore, one may conclude that Pb was accumulated in the root, while Cd and Zn were concentrated in the aerial parts of the Nerium oleander plant. On the other hand, Pb considered one of the heavy metals where it's movement in the plants is slower than Cd and Zn due to its molecular weight is bigger than the latter HMs. Abstract : Phytoremediation, Simple uptake model (UPM), HMs, (Bioaccumulation factors), Nerium oleander ; Agricultural soil science; Environmental science; Soil science; Environmental chemistry; Environmental pollution; Environmental toxicology, Agriculture, Toxicology.